Daya Hasil Dan Adaptasi Beberapa Genotipa Terong (Solanum melongena L.) - Theresia Tan (Fakultas Pertanian Universitas Papua, 2009)
The objective of this experiment was to determine productivity and adaptation of new genotypes of eggplant in Manokwari. The experiment was conducted at Faculty of Agriculture and Agricultural Technology Unipa using completely randomized design which consists of 5 genotypes of eggplant (Mustang, Fortuna, Naga hijau, Kopek, Denmark) as a treatment in three replicates.The results showed that all genotypes of eggplant used had good yield productivity and adaptation in Manokwari. Mustang genotype showed the best yield in length, diameter, size and weight per fruit as well as the total and weight of fruit per plant compared to all tested genotypes. Fruit weight per plant of all genotypes were 2,313 g (Mustang), 1,515 g (Fortuna), 1,380 g (Naga Hijau), 1,076 g (Kopek) and 856 g (Denmark).